Syntactic-semantic relationships in the mental lexicon of aphasic patients - Erdeljac, Vlasta (Array, 2008)
This paper examines the relative values of syntactic-semantic relationships in the mental lexicon of aphasic patients, which were tested within syntagmatic and paradigmatic networks of lexical relations. Semantic relations, such as synonymy, antonomy, and hyperonymy, as well as collocational and coordinational syntactic-semantic relations, were examined simultaneously. Twenty-five subjects diagnosed with nominal aphasia were tested, as well as a control group of 20 healthy subjects. The control group was matched with the aphasic group in terms of dominant hemisphere, age, sex, and job. A naming test based on semantic context was used in this research. The test was presented orally to subjects. After the examiner had read a sentence, subjects were supposed to finish it with a target word (the word which was, through context, in a syntactic-semantic relationship with the rest of the sentence). Sentences were composed of highly frequently occurring words. The categories used in the test were randomly patterned. The resultant data were analysed according to adequate semantic relations of the answers in the given context, and according to the type of the semantic-syntactic relation in 'wrong' answers. Results of this analysis are interpreted according to current psycholinguistic theories.